2022
DOI: 10.3389/fphar.2021.792331
|View full text |Cite
|
Sign up to set email alerts
|

Application Potential of Plant-Derived Medicines in Prevention and Treatment of Platinum-Induced Peripheral Neurotoxicity

Abstract: As observed with other chemotherapeutic agents, the clinical application of platinum agents is a double-edged sword. Platinum-induced peripheral neuropathy (PIPN) is a common adverse event that negatively affects clinical outcomes and patients’ quality of life. Considering the unavailability of effective established agents for preventing or treating PIPN and the increasing population of cancer survivors, the identification and development of novel, effective interventions are the need of the hour. Plant-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…From the foregoing review, the role of natural products in gynecological cancer treatment is constantly well-known, and its clinical value continues to be valued. Research on natural products has gone deep into improving chemotherapy drugs and tumor immunotherapy ( Xu et al, 2021 ). The diversity of polysaccharides depends mainly on their plants or biological sources, and their unique structure helps them successfully apply in the field of gynecological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…From the foregoing review, the role of natural products in gynecological cancer treatment is constantly well-known, and its clinical value continues to be valued. Research on natural products has gone deep into improving chemotherapy drugs and tumor immunotherapy ( Xu et al, 2021 ). The diversity of polysaccharides depends mainly on their plants or biological sources, and their unique structure helps them successfully apply in the field of gynecological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals have potent tumoricidal activity against most cancers [ 102 ]. Moreover, previous reports also claim the neuroprotective properties of phytochemicals against chemotherapy-induced neurotoxicity [ 103 ]. Mohamed et al found that Epicatechin, a polyphenolic molecule from green tea, supplemented orally at dosage of 10 mg/kg/day for 2 weeks prior to doxorubicin injection and then for another 2 weeks with doxorubicin.…”
Section: Possible Therapeutic Intervention For Chemotherapy-mediated ...mentioning
confidence: 99%